THE POSITIVE EFFECTS OF VIDEO GAMES IN TEACHING ENGLISH TO BEGINNER-LEVEL LEARNERS (Scientific journal of the Fergana State University, 2024)
This study investigates the positive effects of video games in teaching English to beginner-level learners. Incorporating video games into language learning environments offers an engaging and interactive approach that enhances vocabulary acquisition, listening skills, and motivation. Through a mixed-method research design involving quantitative assessments and qualitative interviews, this research evaluates the effectiveness of video games in a sample of 50 beginner-level English learners. Results indicate significant improvements in language proficiency, particularly in vocabulary retention and listening comprehension. The findings suggest that video games provide a dynamic and enjoyable learning experience, promoting higher engagement and better language outcomes compared to traditional methods.